MITF Regulates Downstream Genes in Response to Vibrio parahaemolyticus Infection in the Clam Meretrix Petechialis - Zhang, Shujing; Yue, Xin; Yu, Jiajia; Wang, Hongxia; Liu, Baozhong (Frontiers in Immunology, 2019)
The microphthalmia-associated transcription factor (MITF) is a basic helix-loop-helix-leucine zipper protein that plays a key role in cell proliferation, survival and immune defence through the direct transcriptional control of downstream genes. We have found that MITF participates in the immune response to Vibrio parahaemolyticus infection in the clam Meretrix petechialis. In this study, we focused on how MITF functions in immunity. First, PO, CTSK and BCL-2 were identified as the target genes of MpMITF in the clam by RNAi. EMSAs showed direct binding between the MpMITF protein and the E-box of the MpPO, MpCTSK and MpBCL-2 promoters. Yeast one-hybrid assays also suggested that MpMITF could activate the expression of these three downstream genes. These results demonstrated that the transcriptional expression of MpPO, MpCTSK and MpBCL-2 is directly regulated by MpMITF. Second, we analysed the roles of MpPO, MpCTSK and MpBCL-2 in clam immunity. The mRNA expression of MpPO, MpCTSK and MpBCL-2 increased significantly after V. parahaemolyticus challenge, which implied that these genes might take part in the immune defence against V. parahaemolyticus challenge in clams. The purified recombinant proteins, MpPO and MpCTSK, inhibited the growth of V. parahaemolyticus. Additionally, the apoptosis rate of clam haemocytes rose significantly when the activity of MpBCL-2 was suppressed. These results revealed that MpPO, MpCTSK and MpBCL-2 are involved in the immune defence against V. parahaemolyticus. This study supports the idea that the MpMITF pathway plays a key role in immune defence through the direct regulation of the downstream genes MpPO, MpCTSK and MpBCL-2 in the clam, M. petechialis.